THE BAYESIAN SEM APPROACH ON RELIGIOUS TOURISM AND SME'S ENTREPRENEURIAL OPPORTUNITY INTERRELATION IN RURAL AREA - Wulandari, Frilianda; Devianto, Dodi; Yanuar, Ferra (PATTIMURA UNIVERSITY, 2022)
Economics, social and culture are interrelated fields in developing a country. The social and cultural conditions that grow in an area affect how the economy develops in that area and its surrounding. This study analyzed a causal relationship from 60 nascent entrepreneurs at rural area of religious tourism with Bayesian SEM to handle a small amount of data. Based on the results of the analysis, it was found that entrepreneurial motivation and cultural motivation had a significant effect on rural religious tourism. The latent variable of rural religious tourism and entrepreneurial motivation have a significant effect on SME's entrepreneurial opportunity. The entrepreneurial motivation variable has a correlation with the cultural motivation variable.This characteristics has established the Minangkabau heritage of rural area described on its strong religious tourism aspect into SME's entrepreneurial challenge of nascent entrepreneurs.